2014
DOI: 10.1016/j.apacoust.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of writing by background speech: The role of speech transmission index

Abstract: Speech transmission index (STI) is an objective measure of the acoustic properties of office environments and is used to specify norms for acceptable acoustic work conditions. Yet, the tasks used to evaluate the effects of varying STIs on work performance have often been focusing on memory (as memory of visually presented words) and reading tasks and may not give a complete view of the severity even of low STI values (i.e., when speech intelligibility is low). Against this background, we used a more typical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 23 publications
1
38
0
1
Order By: Relevance
“…A number of studies have demonstrated that lower STI (or higher privacy) values for task-irrelevant background speech is associated with greater performance (e.g., Ellermeier and Hellbr€ uck, 1998;Haapakangas et al, 2011;Schlittmeier and Hellbr€ uck, 2009). This holds true in visualverbal serial recall (Ellermeier and Hellbr€ uck, 1998;Ebissou et al, 2013;Schlittmeier and Hellbr€ uck, 2009;Haapakangas et al, 2011) as well as in tasks that require processing of meaning and lexical-based retrieval (Haka et al, 2009;Jahncke et al, 2013;Keus van de Poll et al, 2014;Loewen and Suedfeld, 1992;Venetjoki et al, 2006). Yet, as mentioned above, the reason why background speech is less detrimental when its intelligibility is reduced differs, depending on the task at hand.…”
Section: A Why Sound Disrupts Cognitive Performancementioning
confidence: 82%
See 2 more Smart Citations
“…A number of studies have demonstrated that lower STI (or higher privacy) values for task-irrelevant background speech is associated with greater performance (e.g., Ellermeier and Hellbr€ uck, 1998;Haapakangas et al, 2011;Schlittmeier and Hellbr€ uck, 2009). This holds true in visualverbal serial recall (Ellermeier and Hellbr€ uck, 1998;Ebissou et al, 2013;Schlittmeier and Hellbr€ uck, 2009;Haapakangas et al, 2011) as well as in tasks that require processing of meaning and lexical-based retrieval (Haka et al, 2009;Jahncke et al, 2013;Keus van de Poll et al, 2014;Loewen and Suedfeld, 1992;Venetjoki et al, 2006). Yet, as mentioned above, the reason why background speech is less detrimental when its intelligibility is reduced differs, depending on the task at hand.…”
Section: A Why Sound Disrupts Cognitive Performancementioning
confidence: 82%
“…Another way acoustic maskers can protect performance is, hence, by making it more difficult for the cognitive system to extract meaning from the speech signal-by which disruption that emanates from semantic interference is reduced. Consonant with this, reducing the intelligibility of background speech by superimposing it with a partial masker has been shown to reduce its detrimental effects (e.g., Keus van de Poll et al, 2014).…”
Section: A Why Sound Disrupts Cognitive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic comfort is a complex aspect to evaluate. 6 In fact, the presence of a pleasant sound could considerably improve acoustic comfort, even if its volume is quite high. Perceived intensity therefore needs to be combined with subjective acoustic satisfaction to provide a comprehensive picture of acoustic comfort.…”
Section: Acoustic Comfortmentioning
confidence: 99%
“…Architects and designers should not overlook these influences as they can jeopardize the acoustical environment. 6 Many occupants are not satisfied with the indoor acoustic environment, despite the development of acoustic standards. 7 The response of occupants to noise is unquantifiable and depends on the strength of the emitted signal and the background noise in the receiving situation; a way has to be found to transfer this information and communicate about the issue without forcing people to understand the nature of decibels or the meaning of noise insulation indices.…”
Section: Introductionmentioning
confidence: 99%